Height in Eighteenth-Century Chilean Men: Evidence from Military Records, 1730–1800s - Navarrete-Montalvo, J; Llorca-Jana, M; Araya-Valenzuela, R; Droller, F (Elsevier B.V., 2018)
This article provides the first height estimates for the adult population for any period of Chilean history. Based on military records, it gives an analysis of the average heights of male soldiers in the last eight decades of the colonial period, c.1730–1800s. The average height of Chilean men was around 167 centimetres, making them on average taller than men from Mexico, Italy, Portugal, Spain and Venezuela, but of a similar height to men from Sweden. However, Chilean men were clearly shorter than men in neighbouring Argentina, the USA and the UK. Chilean height remained stable during the 1740–1770s, but it declined by some 2–3 centimetres between the 1780 s and the 1800s, in line with a fall in real wages due to increasing food prices and population growth. © 2018 Elsevier B.V.
Keywords: Biological standard of living; Physical stature; Height; Chile; Anthropometric history; Eighteenth century